2016
DOI: 10.1007/s10658-016-1023-6
|View full text |Cite
|
Sign up to set email alerts
|

The sequevar distribution of Ralstonia solanacearum in tobacco-growing zones of China is structured by elevation

Abstract: Bacterial wilt, caused by Ralstonia solanacearum, is a devastating disease resulting in tremendous losses of economic crops such as plants in the Solanaceae. Recent studies showed that R. solanacearum is spreading from the lowlands to the highlands in China. We studied 97 Chinese R. solanacearum strains that were isolated from four tobacco-growing zones over a wide range of elevations using phylotype specific multiplex polymerase chain reaction (Pmx-PCR) and phylogenetic relationships (egl and mutS). The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 37 publications
3
45
0
1
Order By: Relevance
“…According to the cluster analysis of the partial sequence of egl gene, all Guangdong strains of phylotype I were partitioned into nine previously described sequevars 13, 14, 15, 17, 18, 34, 44, 45, 48 and a new sequevar, revealing that Guangdong strains of phylotype I are phylogenetically diverse. Sequevar 34 was only found on four widespread host plants, tomato, pepper, eggplant and tobacco in Guangdong, which is supported by previously studies (Li et al., ; Liu et al., ; Xu et al., ). Sequevars 15 and 44 were found on many more host plants than other sequevars (Table ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…According to the cluster analysis of the partial sequence of egl gene, all Guangdong strains of phylotype I were partitioned into nine previously described sequevars 13, 14, 15, 17, 18, 34, 44, 45, 48 and a new sequevar, revealing that Guangdong strains of phylotype I are phylogenetically diverse. Sequevar 34 was only found on four widespread host plants, tomato, pepper, eggplant and tobacco in Guangdong, which is supported by previously studies (Li et al., ; Liu et al., ; Xu et al., ). Sequevars 15 and 44 were found on many more host plants than other sequevars (Table ).…”
Section: Discussionsupporting
confidence: 84%
“…Crop losses consistently reach 5% to 80% in bacterial wilt‐infested fields, such as 45% to 80% on tomato, 5% to 25% on eggplant, 13% to 30% on pepper, 10% to 35% on tobacco, 7% to 60% on kencur, 10% to 25% on potato, 8% to 35% on ginger, respectively. Previous research has suggested that R. solanacearum strains from China belong to phylotypes I and II, and includes 12 sequevars (Liu et al., ; Xu et al., ), but information on the diversity of a bacterial population isolated from other crops in Guangdong province is incomplete, making it difficult to develop control methods. It is obvious that a better understanding of the population structure of R. solanacearum strains in Guangdong is needed to develop valid control methods.…”
Section: Introductionmentioning
confidence: 99%
“…In China, phylotype I R. solanacearum strains infecting tobacco display sequevar diversity and are spreading from the lowlands to the highlands and cold areas (Liu et al, 2017). It is interesting to study the genetic variations of R. solanacearum influenced by highland circumstances and host environment.…”
Section: Introductionmentioning
confidence: 99%
“…Genomic DNA was extracted from each isolate. The sequence of 16S ribosomal RNA, endoglucanase precursor (egl) and DNA mismatch repair protein (mutS) were amplified (Liu et al 2017), and blast searches showed 99 to 100% identity with reference sequences of R. solanacearum (GenBank accession Nos. KY594788 and EU348761).…”
mentioning
confidence: 99%
“…All strains generated the 280-bp species-complexspecific fragment and a 144-bp fragment specific to phylotype I of R. pseudosolanacearum (Safni et al 2014). Furthermore, egl and mutS genes from these strains revealed that they were closest to sequevar 13, known to occur in South-East China (Liu et al 2017). Twelve sequences of three isolates were submitted to GenBank (MG840818-MG840829).…”
mentioning
confidence: 99%